Social Security Coverage and Related Factors in Mexican Older Adults: Analysis of Three National Surveys From the Mexican Health and Aging Study - Alvaro García Pérez; Bayron Alexander Sandoval Bonilla; Laura Bárbara Velázquez Olmedo (Advances in Public Health)
Conclusions: In the sample, 60.8% of older adults have access to social security coverage, representing a 6.7% increase on the percentage obtained for the 2015 sample. Identifying the barriers to social security coverage is necessary in order to improve access to the healthcare system and reduce health in equalities for all older Mexican adults.